The Relationship of MSME Owner's Financial Literacy Score and MSMEs Performance (Case Study of MSMEs in School of Business and Management at Institut Teknologi Bandung) - Sijabat, Dedy Syahputra; Faturohman, Taufik (Journal of Innovation, Business and Entrepreneurship, 2017)
Abstract. In the era when Indonesia’s entrepreneurship is growing and increasing, a proper assessment of financial literacy index among the MSMEs owner is very crucial because those index supposed to be one of the factors that determines the success of the business. In the case of MSMEs in School of Business and Management Institut Teknologi Bandung (SBM ITB), it was found that 8 out of 10 of SBM ITB students’ small enterprises are running out of businesses just within 1 or 2 years after its establishment. It was also found that 9 out of 10 businesses in SBM ITB do not have a proper financial management system. Therefore, the researcher in this study wanted to measure the financial literacy score of those MSMEs owners aiming to see its relationship with the performance of the respective MSMEs. Additionally, research or study that sees financial literacy from the point of view of MSMEs owners in Indonesia is still quite low compared to those that see it from an individual/personal point of view. So, this research is also expected to be able to fill the gap. To achieve those goals, ordinal logistic regression analysis is used. The findings are indicative of a significant relationship between financial literacy score with MSME performance in term of managerial experience, expertise in customer service, enterprise culture, and innovation and learning process in term of investment and efficiency of new product development. Keywords: Financial Literacy, MSME Performance, MSME Financial Literacy